Sustained treatment of retinal vascular diseases with self-aggregating sunitinib microparticles - Hiroki Tsujinaka (Nature Portfolio, 2020)
Neovascular age-related macular degeneration and diabetic retinopathy are currently treated with repeated intravitreous injections of VEGF neutralizing proteins. Here the authors develop a microparticle-loaded tyrosine kinase inhibitor therapy, which is effective for six months after a single injection in preclinical models.